Investigation on the microstructural evolution and precipitation hardening mechanism of 1Cr15Ni36W3Ti superalloy with varied C contents. (5th November 2019) - Li, Haoze; Jiang, Bochuan; Gao, Ming; Xing, Weiwei; Ma, Yingche; Liu, Kui
Abstract: Impacts of C content on the microstructural evolution and precipitation hardening mechanism in 1Cr15Ni36W3Ti was studied by phase modelling, microstructural analysis and room-temperature tensile test. The casting material was composed of γ, interdendritic primary MC and secondary MC carbides. The morphology of the primary MC carbide, the amount of which was proportional to the C content, transformed from bulk and short rod-like to skeleton with the C content increasing. The primary MC carbides crushed in pieces during hot working and served as grain-boundary pinning particles during solution treatment. The increased C content made the precipitation of the γ′ phase transform from nucleation dominated to growth dominated at the second-stage aging treatment, which increased the average diameter but lowered the volume fraction of the γ′ phase. Accordingly, the γ′/dislocation interaction transformed from dislocation shearing to complete Orowan looping upon yielding, leading to the declined yield and tensile strength. The coherency strengthening mechanism played an important role in the reinforcement of this alloy. The C content of this kind of superalloy with a low amount of γ′ forming element should be limited below a proper level so as to maximize the coherency strengthening contribution. Graphical abstract: Unlabelled Image Highlights: Impacts of carbon content on microstructure evolution and strengthening mechanism of 1Cr15Ni36W3Ti were investigated. The rising carbon content increased γ' average diameter but decreased γ' volume fraction. Room-temperature yield and tensile strength decreased with carbon content increasing. The γ'/dislocation interaction transformed from dislocation shearing to Orowan looping with carbon content increasing.